Scanning electron microscope examination of the dental enameloid of the Cretaceous durophagous shark Ptychodus supports neoselachian classification. (1st August 2016) - Hoffman, Brian L.; Hageman, Scott A.; Claycomb, Gregory D.
Abstract: Although Ptychodus teeth are well known in Late Cretaceous marine deposits in North America and Europe and a few specimens with jaw elements have been discovered, the taxonomic position of the shark genus Ptychodus is enigmatic due to the lack of preservation of diagnostic material other than teeth. These sharks possessed a pavement dentition suited to a diet of hard-shelled macroinvertebrates (durophagy), leading several studies to variously describe Ptychodus as a batoid, a hybodont shark, or a selachimorph. Members of the Selachimorpha share one dental synapomorphy, a triple-layered enameloid (TLE) consisting of an outer shiny-layered enameloid (SLE) of randomly oriented hydroxyapatite crystallites, a middle layer of parallel-bundled enameloid (PBE), and an inner layer of tangled-bundled enameloid (TBE). Batoids and hybodonts both have teeth with single crystallite enameloid (SCE). We examined teeth from Ptychodus collected from the Lincoln Limestone of the Greenhorn Formation of Barton County, Kansas, and compared their enameloid ultrastructure with that of a Carboniferous hybodontiform and the Cretaceous lamniform shark Squalicorax curvatus Williston, 1900. Scanning electron microscopic examination of Ptychodus shows that crystallite bundling in the form of a TLE is evident in these teeth. The PBE is most apparent at transverse enameloid ridges of Ptychodus teeth. Columns of dentine penetrate into the tooth enameloid, and the crystallites near the dentine are randomly oriented. These observations bolster the argument that Ptychodus is a genus of highly specialized selachimorph shark, rather than a hybodont or batoid.